Final answer:
To solve this problem, you can use the given equation and isolate one of the variables to find the solution.
Step-by-step explanation:
Let's solve the equation:
7x + 6y = 31
where:
x is the first number
y is the second number
To solve for x and y, we can use the substitution method. Let's first express y in terms of x:
y = (31 - 7x) / 6
Now we can substitute this expression for y into the original equation:
7x + 6 × (31 - 7x) / 6 = 31
Simplifying the right side of the equation, we get:
7x + 31 - 7x = 31
Combining like terms, we get:
-7x + 31 = 31
Subtracting 31 from both sides, we get:
-7x = 0
Dividing both sides by -7, we get:
x = 0
Now that we know x, we can substitute it back into the expression for y:
y = (31 - 7 × 0) / 6
Simplifying, we get:
y = 31 / 6
Therefore, the two numbers are x = 0 and y = 31 / 6.